Skateboarding: da transfer??ncia de significado cultural ?? influ??ncia no comportamento do consumidor - Reis, Lucas Cardoso dos (2016)
One of the indications that skateboarding is strong professionalization process in Brazil is the frequent use of the skateboarding subculture in commercials, soap operas and printed advertisements, he characterizes the sport as a way of meaning the product transfer. In line with this context, this study aims to investigate how the cultural significance of transfer occurs when no sports companies use skateboarding in commercials, and how you react to the influences on the behavior of consumers, analyzed in six dimensions: admiration, contempt, meaning transfer to the product, dispersion, perception and purchase intent. It is an exploratory research, with qualitative method, which used two focus groups as the data collection process (practicing and non-practicing) with five participants each, and subsequent content analysis; we used the Atlas Ti software for encoding the collected material. The results show that there are more similarities than differences in consumer behavior between the two, the intention to purchase was declared before the practitioners, however, others admitted that the commercials with skateboarding called attention to the point of the product make If option. The brand recall and elements of the game such as speed, balance, radicalism, wellness area and adrenaline were cited in both groups. The results showed that company VIVO applied best to transfer meaning of skateboarding to the product and the company that got more endurance was the Banco Ita??, due to the presence of a non-legal representative caused noise in communication, especially for individuals who do not practice the mode.